2022
DOI: 10.3390/machines10090782
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Neural-PID Visual Servoing Tracking Control via Extreme Learning Machine

Abstract: The vision-guided robot is intensively embedded in modern industry, but it is still a challenge to track moving objects in real time accurately. In this paper, a hybrid adaptive control scheme combined with an Extreme Learning Machine (ELM) and proportional–integral–derivative (PID) is proposed for dynamic visual tracking of the manipulator. The scheme extracts line features on the image plane based on a laser-camera system and determines an optimal control input to guide the robot, so that the image features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These scholarly documents collectively explore remotely operated vehicles (ROVs) for inspection purposes, encompassing a comprehensive review of inspection-class ROVs, the development of an intelligent support system for ROV operators to enhance real-world performance, and the introduction of a novel control method utilizing terminal sliding mode and dynamic damping to improve fault tolerance and predictive capabilities for tracked ROVs [1][2][3], highlighting the roles of robotic arms. These studies also investigate the impact of machining trajectory on grinding force for complex-shaped stone by a robotic manipulator, apply adaptive neural-PID visual servoing tracking control using an Extreme Learning Machine (ELM), and model impedance control with limited interaction power for a 2R planar robot arm [4][5][6] or manipulators [7,8] in conducting complex underwater tasks beyond human reach. These manipulators, operated via controllers like joysticks, are designed for diverse missions, varying in size and strength, and are equipped with hydraulic or electric power, along with sensory or visual aids.…”
Section: Introductionmentioning
confidence: 99%
“…These scholarly documents collectively explore remotely operated vehicles (ROVs) for inspection purposes, encompassing a comprehensive review of inspection-class ROVs, the development of an intelligent support system for ROV operators to enhance real-world performance, and the introduction of a novel control method utilizing terminal sliding mode and dynamic damping to improve fault tolerance and predictive capabilities for tracked ROVs [1][2][3], highlighting the roles of robotic arms. These studies also investigate the impact of machining trajectory on grinding force for complex-shaped stone by a robotic manipulator, apply adaptive neural-PID visual servoing tracking control using an Extreme Learning Machine (ELM), and model impedance control with limited interaction power for a 2R planar robot arm [4][5][6] or manipulators [7,8] in conducting complex underwater tasks beyond human reach. These manipulators, operated via controllers like joysticks, are designed for diverse missions, varying in size and strength, and are equipped with hydraulic or electric power, along with sensory or visual aids.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various control algorithms seem to work together or nested. [38][39][40]. In [40], the extreme learning machine-PID controller has shown that it outperforms the pure P and PID controllers with the adaptive tuning of the control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40]. In [40], the extreme learning machine-PID controller has shown that it outperforms the pure P and PID controllers with the adaptive tuning of the control parameters. Optimization methods such as GA [38] and PSO [39] are used, especially to select the coefficients of the widely used PID controller.…”
Section: Introductionmentioning
confidence: 99%